(untitled) (Texas Journal of Philology, Culture and History, 2023)
In the article, the author analyzed the possibilities of pilgrimage tourism in the Tashkent region, and the topic was highlighted on the example of one of the places of pilgrimage centers in the Machit Ali region, located in the Parkent district.